Istilah percetakan, penerbitan, dan komunikasi massa, Inggeris-Malaysia-Ingeris (Dewan Bahasa dan Pustaka, Kementerian Pelajaran Malaysia, 1978)
English-Malaysian and Malaysian-English glossary of printing, publishing, and mass communication terms.